Pendekatan Edukatif berbasis Kearifan Lokal dalam Pencegahan Stunting: Pemanfaatan Daun Kelor melalui Media Poster pada Masyarakat Baduy Luar - Wahyuni, Isti Nursih; Fathony, Ivan Issa; Nurhayati, Euis Sri; Fahruroji, Muhammad; Esa, Qiran Ridha (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
Stunting remains a critical public health issue among the Outer Baduy community, significantly affecting children’s growth and cognitive development. One promising local solution is the utilization of Moringa oleifera (moringa leaves), a nutrient-dense superfood with high potential to address nutritional deficiencies. Nonetheless, low levels of nutritional literacy and insufficient knowledge about the advantages and preparation of moringa leaves underscore the importance of delivering education that is both culturally appropriate and easy for the community to understand. This community service program aimed to enhance the Outer Baduy community’s understanding of stunting prevention through the introduction of moringa-based nutrition education. The methods employed included participatory counseling, visual communication using posters and x-banners, and the distribution of simplified educational materials. Direct socialization and collaboration with local leaders ensured effective message delivery and community engagement throughout the program. The findings demonstrated a heightened understanding among participants regarding the significance of balanced nutrition and the promising role of moringa leaves as a sustainable, locally available food resource. This program demonstrates how culturally grounded education can foster behavioral change and community empowerment in improving child nutrition. Moreover, the program plays a role in advancing Sustainable Development Goals (SDGs) 3 (Good Health and Well-being) and 2 (Zero Hunger).